2004
DOI: 10.1139/f04-017
|View full text |Cite
|
Sign up to set email alerts
|

Fish-habitat modeling for gap analysis to conserve the endangered Topeka shiner (Notropis topeka)

Abstract: Decision support tools that predict fish distribution over broad spatial scales are needed to assist in planning watershed management and endangered species recovery. We developed a geographical information system model with multivariate logistic regression to rank valley segments for probable occurrence of the endangered Topeka shiner (Notropis topeka) using stream condition variables (stream size, groundwater potential, channel slope, streamflow, network position) and land-cover variables (percent pasture, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…Filipe et al (2004) used species distribution models, the conservation status of fish, and a GIS to identify the conservation priority of catchments in the Guadiana River basin, Portugal. Others have used predicted species occurrences to identify stream segments and catchments that should be given priority for the conservation of particular species (Wall et al, 2004) or conservation of freshwater biodiversity (Argent et al, 2003;Sowa et al, 2007). Thus, spatially explicit information and GIS are valuable tools for managers who need to identify areas that are to have a fish conservation emphasis (Fisher and Rahel, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Filipe et al (2004) used species distribution models, the conservation status of fish, and a GIS to identify the conservation priority of catchments in the Guadiana River basin, Portugal. Others have used predicted species occurrences to identify stream segments and catchments that should be given priority for the conservation of particular species (Wall et al, 2004) or conservation of freshwater biodiversity (Argent et al, 2003;Sowa et al, 2007). Thus, spatially explicit information and GIS are valuable tools for managers who need to identify areas that are to have a fish conservation emphasis (Fisher and Rahel, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Such models also make it is easier to identify large areas with suitable habitat that then can be targeted for conservation or restoration efforts (Rodrı´guez et al, 2007). For example, Wall et al (2004) modelled the distribution of Topeka shiner (Notropis topeka) by using large-scale geospatial data, and combined its predicted distribution with land protection information to identify areas that should be given high conservation priority. Brewer et al (2007) used their models to predict the distribution of smallmouth bass throughout Missouri, and suggested that predictions could be used to identify stream segments of management interest where smallmouth bass populations were not meeting their natural potential.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an understanding of species-habitat relationships can provide insight into the effects of land use practices, habitat alterations, and climate change on species distributions (Wang et al 2003;Wall et al 2004;Lyons et al 2010). Modeling of species distributions is an important tool for addressing many issues in conservation (Guisan and Thuiller 2005), and the use of predictive occurrence models to further the understanding of fish species' relationships with habitat features in freshwater systems is common (e.g., Olden and Jackson 2001;Rich et al 2003;Steen et al 2008).…”
mentioning
confidence: 99%
“…Fish, and Notropis spp. specifically, have been shown to exhibit habitat-specific choice tendencies (Aadland 1993, Wall et al 2004). …”
Section: Discussionmentioning
confidence: 99%